Ett arkivfynd och dess bakgrund - Seela, Jacob (1997)
The statute proposal dealt with here goes back to a time when the Jewish community in Helsinki predominantly consisted of discharged residents and those serving in the Russian army stationed in Finland, along with their abundant families. They had indeed through an ordinance of 1858 been given the right to settle in the country, but their lives were distressed by crushing poverty and the mistrust of citizenry, and from the beginning the lack of economic rights as well. The inhabitants of the country had vague notions about this foreign minority which on top of everything else belonged to a religion the overwhelming majority considered a threat to Christianity. The authorities, with the senate in the vanguard, with felicitous exceptions, showed a hostile stance. Under such circumstances religion and its practice became the major factor in Jewish life in Helsinki. The formulation of the statute proposal sometimes reveals that from the very early period in the history of the congregation voices were raised in warning that the new generation born and bred in the Finnish capital were not as ready to uphold the tradition of the fathers as might be wished.
Keywords: Civil Rights; Congregations, Jewish; Jews; Finland; Judaism and state